Morphosyntactic Adaptation and Functional Use of English Loanwords in Gen Z Online Service Conversations - Margaret Stevani; Murad Sawalmeh; Happy Kusuma Wardani (OKARA: Jurnal Bahasa dan Sastra, 2026)
The increased prevalence of English in daily Indonesian communication was attributed to the rise of digital commerce and social media. Unlike previous research on code-mixing and borrowing, few studies have investigated how English words were modified in online service chats. This paper investigated how Indonesian Gen Z users transformed English words morphosyntactically in their conversations. It analyzed 124 chat interactions collected from Shopee, Tokopedia, Instagram, and WhatsApp. Using qualitative analysis, the study identified recurring morphosyntactic processes, including clipping, affixation, permutation, and hybrid command formation. Examples included "notif” (from notification), “orderan” (order + -an), “di-scan” (scan with the Indonesian passive prefix di-), and “auto-panik” (automatically panic). These forms showed that English words were restructured to fit Indonesian linguistic patterns, becoming integrated into everyday digital communication rather than remaining isolated loanwords. Interview data revealed that users employed these forms to make communication more efficient, distinctive, humorous, and socially engaging. The findings confirmed that Indonesian youth actively modified English words to support efficient, creative, humorous, and interactive communication. These usage patterns contributed to ongoing changes in Indonesian digital communication.